Respondent or non-respondent comparison post cardiac resynchronisation therapy implantation in patients with dilated cardiomyopathy - Roy, Bidyut; Haque, M. Azizul; Paul, Kaushik; Mandal, Sankar Chandra (International Journal of Research in Medical Sciences, 2023)
Background: Dilated cardiomyopathy can be treated using cardiac resynchronisation therapy (CRT) effectively. In our study, we compared the clinical and biochemical profile of responders and non-responders to CRT device (CRTD) implantation suffering from DCM. Methods: A cross-sectional observational study was performed in 47 patients with dilated cardiomyopathy for CRTD implantation for a period of 18 months. The tools used for the study include electrocardiography 12 lead, echocardiography: 2D, M mode, Doppler, strain echo, Holter monitoring, coronary angiography and CRTD implantation. Statistical analysis was performed using Epi Info (TM) 7.2.2.2. Results: The proportion of responders (68.1%) was significantly higher than non-responder (31.9%). Almost 60% of patients in non-responder group had smoking as a risk factor. Around 60% were suffering from hypertension and 33% from T2DM in non-respondent group. Parameters of dyssynchrony has significantly improved in responder group than in non-responder group. LVEDV, LVESV has shown an increase and EF has decreased considerably in DCM patients. Many patients in non-responder category have shown mitral and tricuspid regurgitation. Strain echocardiography parameters-GLS, GRS and GCS were significantly decreased. Post CRTD echocardiographic parameter has improved considerably and LVESV was reduced in more than 15% of responders. Conclusions: The CRTD implantation improves patients’ clinical and Echocardiographic data which can help in better patient management, improving quality of life and decreased healthcare cost. By this study we can improve patients’ selection and predict accordingly for CRT responders and non-responders and can take necessary measures for better patient’s management.